2016
DOI: 10.1111/add.13633
|View full text |Cite
|
Sign up to set email alerts
|

Drinking with mixed-gender groups is associated with heavy weekend drinking among young adults

Abstract: Aims To investigate how gender composition of the drinking group affects young adults’ alcohol consumption on weekend evenings over and above the effect of drinking-group size. Design Using the Internet-based cell phone-optimized assessment technique (ICAT), participants completed online questionnaires on their cell phones every hour from 8 p.m. to midnight on Thursday, Friday, and Saturday evenings over five consecutive weekends. Setting French-speaking Switzerland. Participants Convenience sample of 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 48 publications
3
48
1
Order By: Relevance
“…In addition, participants were asked about the presence of other smokers (yes/no), their relationship to the people who were smoking (e.g., friend, family), and the number of other smokers around (0, 1, 2‒4, 5‒20, and more than 20). To approximate a continuous number of other smokers for analysis, midpoints of categories were used; 23.5 was used for the highest category, as suggested by previous EMA studies (Thrul and Kuntsche, 2015; Thrul et al, 2017). …”
Section: Methodsmentioning
confidence: 99%
“…In addition, participants were asked about the presence of other smokers (yes/no), their relationship to the people who were smoking (e.g., friend, family), and the number of other smokers around (0, 1, 2‒4, 5‒20, and more than 20). To approximate a continuous number of other smokers for analysis, midpoints of categories were used; 23.5 was used for the highest category, as suggested by previous EMA studies (Thrul and Kuntsche, 2015; Thrul et al, 2017). …”
Section: Methodsmentioning
confidence: 99%
“…While contrary to most research indicating that more men consume alcohol than women, recent studies have shown that in young adults, more women tend to drink and consume higher volumes of alcohol when drinking in mixed gender settings, which is typical in college settings [25,26]. Interventions on alcoholic beverage drinking in colleges and universities may need to address the high proportion of female alcohol drinkers.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, it is unlikely that biological sex directly causes differential rates of recanting. Instead, sex differences in recanting may arise in response to other unexamined proximal factors such as peer group gender composition (Thrul et al, 2017) and gender-specific peer influence on drinking (Gaughan, 2006) that may drive observed sex differences. Investigating potential mechanisms for underlying sex differences is an important direction for future research.…”
Section: Discussionmentioning
confidence: 99%